THE EFFECT OF PINEAPPLE COMPOST ON THE GROWTH AND YIELD OF RED OKRA PLANTS IN RED YELLOW PODSOLIC SOIL - Jesica Tasia Ginting, Astina, Dwi Zulfita, Jesica Tasia Ginting (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT This study aimsed to obtain the best dose of pineapple compost on the growth and yield of red okra on Red Yellow Podsolic soil. This research was conducted from November 1, 2018 to January 24, 2019. The statistical method used was Completely Randomized Design consisted of 5 treatments, 5 replications, a each treatment consisted of 4 sample plants. The treatment were (b1) 400 g / polybag, (b2) 800 g / polybag, (b3) 1,200 g / polybag, (b4) 1, 1,600 g / polybag and (b5) 2,000 g / polybag. The variables observed in this study were chlorophyll leaf (unit velocity), root volume (cm3), total leaf area (cm2) dry weight (g), number of fresh fruit (g) and weight of fresh fruit (g). The results showed that the best dosage of pineapple waste was not found for growth and yield of red okra in Yellow Podsolic soil but the effective dosage was indicated by the provision of pineapple waste bocation 15% dose equivalent to 1,200 g / polybag. Key words: Okra, red yellow podsolic soil, pineapple compost